Stigma Peserta Didik terhadap Guru BK: Dampak terhadap Konseling dan Etika Profesional - Alvia Rahmadzani; Maya Rahadian Septiningtyas; Lobby Loekmono (Jurnal Pendidikan Sosial Dan Konseling, 2026)
Students' perception of school guidance and counseling (BK) teachers in Indonesia remains marked by persistent negative stigma, with BK teachers often labeled as "school police" rather than supportive companions. This study aims to analyze the forms of students' negative perceptions and stigma toward BK teachers, identify their underlying factors, examine their impact on service utilization and working alliance quality, and analyze their implications for counselor professional ethics and competence. Using a thematic narrative literature review of national and international journal articles alongside the Indonesian Guidance and Counseling Code of Ethics (ABKIN, 2018), findings were synthesized into major themes and an integrative model. Results show that stigma emerges through personal experience, disciplinary school culture, and limited professional competence in assessment and communication, weakening Bordin's (1979) working alliance components goal, task, and bond and consequently reducing service utilization despite adequate awareness. This condition reveals a gap between normative ethical principles and everyday relational practice. The study proposes an integrative four stage model service experience, school culture, counseling relationship quality, and perceived professionalism as a framework linking previously fragmented findings and offering a conceptual basis for strengthening BK teachers' professional image.